Influence of Social Media on Sexualized Drug Use and Chemsex Among Chinese Men Who Have Sex With Men: Observational Prospective Cohort Study - Wang, Zixin; Yang, Xue; Mo, Phoenix K H; Fang, Yuan; Ip, Tsun Kwan Mary; Lau, Joseph T F (JMIR Publications, 2020)
BackgroundSexualized drug use (SDU; the use of any psychoactive substance before or during sexual intercourse) is prevalent among men who have sex with men (MSM) and may aggravate the worsening HIV epidemic in this key population. ObjectiveThis observational prospective cohort study investigated factors predicting the occurrence of SDU within a 6-month follow-up period among a sample of MSM in Hong Kong. We hypothesized that perceptions related to SDU would mediate the association between the influence of social media/gay social networking apps and SDU during the follow-up period. MethodsParticipants were Chinese-speaking men in Hong Kong, China who had anal intercourse with at least one man in the past year. Among 600 participants who completed the baseline telephone survey, 407 (67.8%) completed another telephone survey 6 months later. Logistic regression models and path analysis were fitted. ResultsAt Month 6, 6.9% (28/407) and 4.4% (18/407) of participants reported SDU and chemsex during the follow-up period. After adjustment for significant baseline background variables (use of pre-exposure prophylaxis; history of HIV and other sexually transmitted infections; anal intercourse with nonregular male sex partners, condomless anal intercourse with men, multiple male sex partnerships, and SDU at baseline), three constructs of the Theory of Planned Behavior (TPB) were significantly associated with SDU during the follow-up period: (1) positive attitudes toward SDU (adjusted odds ratio [AOR] 1.19, 95% CI 1.05-1.36), (2) perceived support for SDU from significant others (AOR 1.15, 95% CI 1.01-1.30), and (3) perceived behavioral control of refraining from SDU (AOR 0.76, 95% CI 0.59-0.98). Exposure to information supporting SDU on social media and gay social networking apps was also significantly associated with SDU (AOR 1.11, 95% CI 1.01-1.22). Bootstrapping analyses indicated that social media influence was indirectly associated with SDU through TPB-related perceptions of SDU (β=.04; B=.002, 95% CI 0.001-0.01). ConclusionsSocial media and gay social networking apps may be a major source of influence on MSM's perceptions and actual behaviors related to SDU.